2021
DOI: 10.1021/acsaem.1c02129
|View full text |Cite
|
Sign up to set email alerts
|

3D Bi2Te3 Interconnected Nanowire Networks to Increase Thermoelectric Efficiency

Abstract: 3D interconnected nanowire scaffoldings are shown to increase the thermoelectric efficiency in comparison to similar diameter 1D nanowires and films grown under similar electrodeposition conditions. Bi 2 Te 3 3D nanonetworks offer a reduction in thermal conductivity (κ T ) while preserving the high electrical conductivity of the films. The reduction in κ T is modeled using the hydrodynamic heat transport equation, and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 33 publications
(54 reference statements)
1
11
0
Order By: Relevance
“…To develop a comprehensive theory predicting the measured κ in both the metalattice and a broader class of highly confined nanostructured systems, ,, we combine a phonon hydrodynamics framework and the theory of rarefied gas dynamics in porous media. , Previous work has demonstrated that nanoscale size and frequency effects on heat transport in silicon can be modeled in terms of nonlocal and memory effects, as described by the Guyer–Krumhansl equation (GKE), with ab initio geometry-independent coefficients. ,,, However, the predictive capabilities of this hydrodynamic-like approach are restricted to systems with dimensions sufficiently large compared to the average bulk phonon MFP, since nanoscale confinement modifies the ab initio phonon properties used to determine the GKE coefficients. , This excludes the present metalattice and a broader class of nanostructured silicon materials.…”
mentioning
confidence: 99%
“…To develop a comprehensive theory predicting the measured κ in both the metalattice and a broader class of highly confined nanostructured systems, ,, we combine a phonon hydrodynamics framework and the theory of rarefied gas dynamics in porous media. , Previous work has demonstrated that nanoscale size and frequency effects on heat transport in silicon can be modeled in terms of nonlocal and memory effects, as described by the Guyer–Krumhansl equation (GKE), with ab initio geometry-independent coefficients. ,,, However, the predictive capabilities of this hydrodynamic-like approach are restricted to systems with dimensions sufficiently large compared to the average bulk phonon MFP, since nanoscale confinement modifies the ab initio phonon properties used to determine the GKE coefficients. , This excludes the present metalattice and a broader class of nanostructured silicon materials.…”
mentioning
confidence: 99%
“…In the case of nickel ( Figure A1 b), the diffraction pattern obtained for the three different nanostructures show only peaks corresponding to the face-centered cubic (FCC) structure, demonstrating that it is a polycrystalline material. It is worth mentioning here that these kinds of nanostructures have already been fabricated and measured in previous works of our group (see, for instance, [ 33 , 35 , 36 , 39 , 40 ]), which has the expertise of controlling the growth parameters in such a way that the nanostructures obtained are highly reproducible.…”
Section: Resultsmentioning
confidence: 99%
“…Despite the different origins of the plasmon capabilities of the two materials, the results indicate that the optical response is determined by plasmon resonances, whose position depends on the nanowire interactions and material properties. Furthermore, given that Bi 2 Te 3 3D nanowire networks outperform their bulk or thin film counterparts regarding their thermoelectric efficiency [ 40 ] and that these metamaterials can be used to fabricate miniaturized thermoelectric generators, where establishing a thermal gradient can be challenging, the possibility of obtaining an additional localized temperature increase by using these plasmon resonances would result in an increase in the final power output. In our case, the light confinement produced by the plasmonic resonance in the Bi 2 Te 2 1D and 3D nanostructures would increase the effective thermal gradient in the material, and thus, increase the thermoelectric power output obtained in the nanostructured material.…”
Section: Discussionmentioning
confidence: 99%
“…However, due to its promising thermoelectric properties, ScN is much desired in recent times. The ScN thin films exhibit a high thermoelectric power factor of (2–3.5) × 10 –3 W/(m·K 2 ) in the 600–840 K temperature range that is higher than the power factor of most well-established thermoelectric materials such as Bi 2 Te 3 , Bi 2 Se 3 , and PbTe. Such a high power factor in ScN arises from its high electron concentration in the (1–5) × 10 20 cm –3 range due to the presence of unwanted impurities such as oxygen and possible nitrogen vacancies. Molecular beam epitaxy (MBE) and sputter-deposited ScN films also exhibit moderately large mobility in the 90–120 cm 2 /(V·s) range. , However, the highest mobility of 284 cm 2 /(V·s) is reported in hybrid vapor phase epitaxy (HVPE)-deposited ScN films . Mg–hole doping has been used recently to reduce the carrier concentration in ScN, and p-type ScN films with a large Seebeck coefficient are demonstrated. , X-ray absorption spectroscopy (XAS), X-ray photoelectron spectroscopy (XPS), and ultraviolet photoemission spectroscopy (UPS) measurements have shown that both the unwanted n-type oxygen impurity and p-type Mg–hole doping do not introduce defect states inside the band gap, and the rigid band electronic structure remains unchanged with respect to the dopant introduction. , …”
Section: Introductionmentioning
confidence: 99%